Traditional Change in Processions Wedding Malay of Lingga Distric - Atikha Dwi Saputri; Sri Wahyuni; Emmy Solina (IAIN Parepare, 2023)
Culture is taste, creativity and intention, culture is the result of human production itself, culture always lives side by side with tradition. This study aims to determine changes in tradition at each stage of the Malay community wedding procession in Daik Village, Lingga District. This study uses the theory of social change which is used as a knife for analyzing changes in tradition. The informants in this study were six people, namely traditional leaders and several people in the Daik Village, Lingga District. This research method is descriptive qualitative and the selection of informants uses a purposive sampling technique with several predetermined criteria. Data collection techniques include observation, interviews and document review, while data analysis techniques include data collection, data presentation, data reduction to drawing conclusions. The results of the study show that there are many changes in tradition that occur in every stage of the Malay community wedding procession in the past with the present Malay community wedding stages, several processions that have undergone changes, namely at the pre-wedding stage, the marriage process until the end of the wedding, some changes in traditions between traditions matchmaking, the tradition of merisik, the tradition of sending shopping, the tradition of pawn cupak, the tradition of hanging, the tradition of picking up, the tradition of porches, the tradition of small henna, the tradition of maulud berzanzi, the tradition of berulus bathing and the tradition of redeeming cupak, which later underwent changes because it was influenced by several factors. Including factors of people's mindset, community education, technological developments and foreign cultural influences.